Failure Analysis of Stainless Steel Lanyard Wire Rope (International Journal of Engineering Materials and Manufacture, 2018)
Present work describes the failure analysis of AISI 304 stainless steel lanyard wire rope which has failed during application in humid atmosphere. The wire rope has 7Â´19 construction which means that it consists of seven strands and each strand having 19 wires twisted in a helical fashion. The microstructures and properties of failed wire rope have been investigated and compared with unused wire rope. Both the periphery and fracture surface of the wire rope display the presence of corrosion debris enriched with O and Cl. The fracture surfaces of the failed and unused wire ropes display intergranular and dimples, respectively. The lanyard wire rope has been exposed in corrosive atmosphere and failed in intergranular mode due to enrichment of O and Cl along the grain boundaries.